Muddling through the Pandemic: Making Sense of Russia’s Confusing Response to COVID-19 - Maltseva, Elena (Ревија за социјална политика/Journal of Social Policy, 2021)
This paper examines the Russian government response to Covid-19, which proved to be ineffective at keeping the virus under control and mitigating the negative socioeconomic effects of the pandemic. It argues that the causes of the Russian government’s suboptimal response to Covid-19 can be attributed to two main factors. First, the authoritarian and overly centralized structure of Russia’s political institutions, which prioritized political and economic considerations over public safety and inhibited genuine regional initiative, undermined the government’s ability to contain the pandemic. The regional heads often lacked the skills, financial resources and authority to implement the necessary policies and containment measures, resulting in disastrous developments in several Russian regions. Second, the Soviet legacies associated with a culture of non-disclosure and the inconsistent public health messaging during the pandemic, combined with limited social relief and economic support measures, contributed to the public mistrust in state institutions, indicating fraught relations between citizens and the state. This was reflected in public protests and popular resistance to government orders, including the widespread defiance of lockdown instructions, a refusal to wear masks in public places and low vaccination rates. Looking ahead, the long-term consequences of the current public health crisis could be deeply political, contributing to a further schism between the rulers and the ruled.
Keywords: Russia; Covid-19; pandemic; governance; vaccination; Sputnik V